Managing Lebanese SMEs During the Pandemic and The Financial Crisis: A Quantitative Research - Maria FRANGIEH (Communications of International Proceedings, 2022)
Nowadays, the Lebanese SMEs are facing the outbreak of two unanticipated crises, the Covid-19 pandemic and the financial collapse. This is perhaps a convenient time to witness the defense tactics used by their owners that will make them either soar or collapse at the end. The fact that researches which depict the importance of leader and follower relationship in SMEs in times of crisis in Lebanon were somehow rare renders this article even more interesting. SMEs are family owned enterprises where the owners often play the role of leaders and managers at the same time. This fact collaborated in spreading a belief, a rather false one, that all managers are leaders and vice versa. From this standpoint, this article’s objective is to clarify the difference between two leadership styles: the participative and the autocratic. The selected approach was quantitative. Data was collected through a survey conducted during January 2022 with sixteen owners-managers in the software field whose enterprises survived the first two years of the crises. This field was specifically selected due the emerged importance of websites development following the Covid-19 disaster, which had extensively shifted the nature of business operations toward an online basis. The respondents were asked about their managing styles during this critical period. The results indicated that SMEs owners are able to accomplish and display both roles as per the situation presented.
Keywords: Autocratic leader; Leadership; Management; Participative leader; SMEs